To find the zeros of the quadratic function \( y = -3x^2 + 12x + 15 \), we can set the equation equal to zero and solve for \( x \):
\[ -3x^2 + 12x + 15 = 0 \]
Now, we can either use the quadratic formula or factor the equation. First, let’s simplify it by dividing every term by -3:
\[ x^2 - 4x - 5 = 0 \]
Next, we can factor this quadratic equation:
\[ (x - 5)(x + 1) = 0 \]
Setting each factor equal to zero gives us:
\[ x - 5 = 0 \quad \Rightarrow \quad x = 5 \]
\[ x + 1 = 0 \quad \Rightarrow \quad x = -1 \]
The zeros of the equation are \( x = 5 \) and \( x = -1 \). So, we can express the zeros as points:
\[ (5, 0) \quad \text{and} \quad (-1, 0) \]
Therefore, the correct response is:
\[ (-1, 0)(5, 0) \]
So the answer is:
(−1, 0)(5, 0)